Pendampingan Manajemen Dan Kelembagaan Bumdes Bumdes Management And Institution Assistance - Siswadi Sululing; Yanti Mutalib (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This Community Service activity was carried out in Sapelang Village, South Buko District with the topic